The Philosophy of Divine Love (ʿIshq) in Sufism and Its Application in Psychospiritual Therapy: A Critical Analysis of al-Niffārī’s Kitāb al-Mawāqif - Achmad, Adang Darmawan; Subhan, Subhan; Qotadah, Hudzaifah Achmad; Al Faruq, Abdillah Achmad (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
This article explores the philosophical and practical dimensions of Ishq Ilāhī (Divine Love) within the classical Sufi tradition, focusing on the seminal work al-Mawāqif by al-Niffārī, a 10th-century CE (4th-century AH) mystic renowned for his profound existential and spiritual expressions. In Sufism, Ishq represents the pinnacle of the spiritual relationship between the servant and the Divine, transcending ordinary love (maḥabbah) and serving as a transformative force that purifies the soul and dissolves the ego in the Divine Presence. This study employs a qualitative approach through document analysis and hermeneutic interpretation of the al-Mawāqif manuscript. The findings indicate that Ishq in this text is not merely a theoretical concept but a practical path of spiritual healing, characterized by ecstatic experiences (wajd), ego annihilation (fanāʾ), and spiritual subsistence (baqāʾ). Furthermore, the article argues that the values and experiential insights of Divine Love can be contextually adapted for contemporary psychospiritual therapy, particularly in addressing issues of existential void, spiritual crisis, and inner psychological distress. This study thus opens an interdisciplinary dialogue between classical Sufism and modern spiritual psychology, positioning Islamic mystical heritage as a potential source of holistic healing and inner transformation. Abstrak Artikel ini mengkaji secara filosofis dan aplikatif konsep Ishq Ilāhī (cinta Ilahi) dalam khazanah tasawuf klasik dengan fokus pada kitab al-Mawāqif karya al-Niffārī, seorang sufi mistikus abad ke-4 H/10 M yang dikenal dengan ungkapan-ungkapan eksistensial dan spiritual yang mendalam. Dalam tradisi tasawuf, ishq merupakan puncak dari hubungan spiritual antara hamba dan Tuhan yang melampaui cinta biasa (maḥabbah), menjadi kekuatan transformatif yang memurnikan jiwa dan meleburkan ego dalam kehadiran Ilahi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi dokumen dan analisis hermeneutik terhadap naskah al-Mawāqif. Temuan menunjukkan bahwa ishq dalam kitab ini bukan hanya bersifat teoretis, tetapi menjadi jalan praksis penyembuhan spiritual melalui pengalaman ekstasis, kehancuran ego (fanā’), dan pencerahan spiritual (baqā’). Lebih lanjut, artikel ini mengusulkan bahwa nilai-nilai dan pengalaman cinta Ilahi dapat diadaptasi secara kontekstual dalam terapi psikospiritual modern, khususnya untuk membantu individu yang mengalami kekosongan makna hidup, krisis eksistensial, dan tekanan psikis yang bersifat spiritual. Studi ini membuka ruang interdisipliner antara tasawuf dan psikologi spiritual kontemporer dengan menjadikan warisan mistik Islam sebagai sumber terapi dan penyembuhan holistik.